Heuristik Dalam Aktivitas Akutansi - Fitria Asas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main aim of this study is to investigate the role of heuristic techniques and cognitive biases in investment decision making and suggest directions for further research. This research uses literature review techniques to understand heuristics and biases that are important in financial behavior and influence investment decisions. This article provides a conceptual overview of the impact of heuristic techniques and cognitive biases in investment decision making. The results of the conceptual analysis show that currently investors use heuristics to minimize losses and maximize profits, but this often leads to systematic decision making errors. This paper advises investors to prioritize financial literacy as a prerequisite for making capital market investment decisions and minimize over-reliance on heuristic techniques, which are often misleading. This research is the first to focus on the impact of cognitive heuristics and biases, informing investment decisions, and suggests directions for future research. This article provides a better understanding of the behavioral finance approach to investment decision making.